PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, PEMBELAJARAN ORGANISASI, DAN INOVASI ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN BADAN USAHA MILIK DESA DI PROVINSI JAWA TENGAH - Ali Sofwan (Tinta Nusantara 2018 Vol.1, 2022)
This study aims to examine and analyze the influence of transformational leadership on organizational learning and organizational innovation in the village owned business entity (bumdes) province of central java and emphasize the importance of providing empirical results that prove this relationship. The research is also to show the positive relationship between organizational learning and organizational innovation on job satisfaction and employee performance in the village owned business entity (bumdes) province of central java. The results showed that transformational leadership style affects organizational learning.